Analisis Laporan Keuangan Pada PT Unilever Indonesia Tbk - Siti Diva Syarifah Lukman (Amsir Management Journal, 2021)
This study aims to determine whether the financial performance of PT. Unilever Indonesia, Tbk is good when measured based on the analysis of liquidity ratio, solvability ratio, profitability ratio, and activity ratio in the last three years. Based on the results of the calculation of financial performance, the liquidity ratio has fluctuated, in 2019 the current ratio decreased by 0,65% due to a high rate of increase in current debt per year. In contrast to the ratio of profitability and activity, both ratios after being analyzed have increased. It can be seen from the calculation of the profitability ratio in 2019 that return on assets decreased by 50% due to an increase in profit before tax and a decrease in total assets from the average total assets but still generate good profits for the company. While the activity ratio in 2017-2019 the activity ratio experienced a good increase from all types of financial ratio, although it decreased in 2019, Assets Turn Over was 2,32. But still, no effect because turn over continues to increase. Well, PT. Unilever Indonesia, Tbk is known that’s the company’s performance of all liquidity ratio, solvability ratio, profitability ratio, and activity ratio is not all good and this answer the author’s hypothesis.